Analisysis of Factor That Affect the Opinion of the BPK Regional Financial Gavernment Report In Indonesia - Sunarti, Lucfia Anissatul A, Aris Eddy Sarwono Dewi Saptantinah & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study is to know BPKâs opinion on the local governmentfinancial report is the factor of discovery of the number of cases of regulatorynoncompliance and the discovery of the potential value of state losses, on thequality of audit opinions on the financial statements of regional gevernments inindonesia. This research mothod is done by census. Sampling technique using themethod of sampling with porposive sampling. With sampling based on subjectiveconsiderations. The purpose of this study is to determine the level of unity ofregulation to the quality of the audit opinion of local financial statements inindonesia and to determine the effect of potential state losses on the quality of auditopinion of local financial statements in indonesia. Analysis motion used multiplelinear regression analysis through by program eviews 9. The results of this studyshow that the number of cases of noncomliance and regulation the amount ofpotential value of the state losses has a negative affect on BPKâs opinion on thefinancial statements of local governments in indonesia.Kaywords: Audit opinion; Number of cases of noncompliance regulation; Case value of potentiallosses of the country.